The Commodification of Childhood The Children's Clothing Industry and the Rise of the Child Consumer - Cook, Daniel Thomas (Duke University Press, 2004)
In this revealing social history, Daniel Thomas Cook explores the roots of children's consumer culture-and the commodification of childhood itself-by looking at the rise, growth, and segmentation of the children's clothing industry. Cook describes how in the early twentieth century merchants, manufacturers, and advertisers of children's clothing began to aim commercial messages at the child rather than the mother. Cook situates this fundamental shift in perspective within the broader transformation of the child into a legitimate, individualized, self-contained consumer.The Commodification of Childhood begins with the publication of the children's wear industry's first trade journal, The Infants' Department, in 1917 and extends into the early 1960s, by which time the changes Cook chronicles were largely complete. Analyzing trade journals and other documentary sources, Cook shows how the industry created a market by developing and promulgating new understandings of the "nature," needs, and motivations of the child consumer. He discusses various ways that discursive constructions of the consuming child were made material: in the creation of separate children's clothing departments, in their segmentation and layout by age and gender gradations (such as infant, toddler, boys, girls, tweens, and teens), in merchants' treatment of children as individuals on the retail floor, and in displays designed to appeal directly to children. Ultimately, The Commodification of Childhood provides a compelling argument that any consideration of "the child" must necessarily take into account how childhood came to be understood through, and structured by, a market idiom
Description based on online resource; title from PDF title page (publisher's Web site, viewed 12. Dez 2020)
Keywords: SOCIAL SCIENCE / Children's Studies; Adolescence -- United States -- History; Child consumers -- United States -- History; Children -- United States -- History; Children's clothing industry -- United States -- History; Mother and child -- United States -- History; Teenage consumers -- United States -- History